Staging, Neurocognition and Social Functioning in Bipolar Disorder - Tatay-Manteiga, Amparo; Correa-Ghisays, Patricia; Cauli, Omar; Kapczinski, Flavio P.; Tabarés-Seisdedos, Rafael; Balanzá-Martínez, Vicent (Frontiers in Psychiatry, 2018)
Introduction: Bipolar disorder (BD) is associated with significant neurocognitive and functional impairment, which may progress across stages. The ´latent stage´ of BD remains understudied. This cross-sectional study assessed staging, neurocognition and social functioning among BD patients and their healthy siblings. Methods: Four groups were included: euthymic type I BD patients in the early (n=25) and late (n=23) stages, their healthy siblings (latent stage; n=23) and healthy controls (n=21). All 92 subjects underwent a comprehensive neuropsychological battery of processing speed, verbal learning/memory, visual memory, working memory, verbal fluency, executive cognition and motor speed. Social functioning was assessed using the FAST scale. Results: Siblings’ social functioning was identical to that of controls, and significantly better than both early- (p<0.005) and late- (p<0.001) stage patients. Although all patients were strictly euthymic, those at late stages had a significantly worse social functioning than early-stage patients (p<0.001). Compared to controls, increasingly greater neurocognitive dysfunction was observed across stages of BD (F=1.59; p=0.005). Healthy siblings’ performance lied between those of controls and patients, with deficits in tasks of processing speed, executive attention, verbal memory/learning, and visual memory. Both early- and late-stage patients had a more severe and widespread dysfunction than siblings, with no significant differences between them. Conclusions: Genetic vulnerability to BD-I seems to be associated with neurocognitive impairments, whereas social dysfunction would be the result of the clinical phenotype. Staging models of BD should take into account these divergent findings in the latent stage.